On Feasibility of Post-Quantum Cryptography on Small Devices. Issue 6 (2018) - Malina, Lukas; Popelova, Lucie; Dzurenda, Petr; Hajny, Jan; Martinasek, Zdenek
Abstract: In this work, we investigate the feasibility of post-quantum cryptography in small and constrained devices such as those used for mobile and Internet-of-Things networks. We describe our experimental post-quantum cryptography implementations on small devices with different platforms. Then, we present and compare the performance results of chosen post-quantum key exchange schemes and their message sizes on selected ARM devices. In addition, we discuss the perspective types of post-quantum cryptographic schemes for various IoT systems with different requirements.